In Older Adults the Antidepressant Effect of Repetitive Transcranial Magnetic Stimulation Is Similar but Occurs Later Than in Younger Adults - Cotovio, Gonçalo; Boes, Aaron D.; Press, Daniel Z.; Oliveira-Maia, Albino J.; Pascual-Leone, Alvaro (Frontiers in Aging Neuroscience, 2022)
Background: Treatment resistant depression is common in older adults and treatment is often complicated by medical comorbidities and polypharmacy. Repetitive transcranial magnetic stimulation (rTMS) is a treatment option for this group due to its favorable profile. However, early influential studies suggested that rTMS is less effective in older adults. This evidence remains controversial. Methods: Here, we evaluated rTMS treatment outcomes in a large international multicenter naturalistic cohort of >500 patients comparing older versus younger adults. Results: We show that older adults, while having similar antidepressant response to younger adults, respond more slowly, which may help explain differences from earlier studies when the duration of a treatment course was shorter. Conclusions: Such evidence helps to resolve a long-standing controversy in treating older depressed patients with rTMS. Moreover, these findings provide an important data point in the call to revise policy decisions from major insurance providers that have unfairly excluded older adults.